Development of an Electronic Volunteer Management System (e-VMS) for Selangor Civil Defence Department using the I.S.O.T.U.R.E model / Habsah Minhat - Minhat, Habsah (2007)
Selangor Civil Defence Department is a subunit of Malaysia Civil Defence Department. Located at Jalan Bunga Raya ,Klang this center of voluntarily become the most known organization by Malaysian as JPAS.As a volunteer center, this organization has a problem to manage record for each volunteer registered within this unit. This is because Selangor Civil Defence Department currently manages a record for volunteer through filing system. Beside associating with a redundancy in each record, this also create a problem to level of management to manage a numbers of volunteer registered.Thus this project developed an electronic volunteer management system for Selangor Civil Defence Department. This web application developed based on a model called as I.S.O.T.U.R.E Model by Boyce, 1971. This model has been used for this project because most it was a standard model for volunteer development program.